Advances in Regenerative Orthopaedics - Evans, Christopher H. (2013)
Orthopaedic injuries are very common and a source of much misery and economic stress. Several relevant tissues, such as cartilage, meniscus and intra-articular ligaments, do not heal. And even bone, which normally regenerates spontaneously, can fail to mend. The regeneration of orthopaedic tissues requires four key components: cells, morphogenetic signals, scaffolds and an appropriate mechanical environment. Although differentiated cells from the tissue in question can be used, most cellular research focuses on the use mesenchymal stem cells (MSCs). These can be retrieved from many different tissues, and one unresolved question is the degree to which the origin of the cells matters. Embryonic and induced, pluripotential stem cells are also under investigation. Morphogenetic signals are most frequently supplied by individual, recombinant growth factors or native mixtures provided by, for instance, platelet-rich plasma; MSCs are also a rich source of trophic factors. Obstacles to the sustained delivery of individual growth factors can be addressed by gene transfer or smart scaffolds, but we still lack detailed, necessary information on which delivery profiles are needed. Scaffolds may be based upon natural products, synthetic materials, or devitalized extracellular matrix. Strategies to combine these components to regenerate tissue can follow traditional tissue engineering practices, but these are costly, cumbersome and not well suited to treating large numbers of individuals. More expeditious approaches make full use of intrinsic biological processes in vivo to avoid the need for ex vivo expansion of autologous cells and multiple procedures. Clinical translation remains a bottleneck.